BCD spectrophotometry for massive stars in transition phases - Aidelman, Yael Judith (2023)
Context. Stars in transition phases, such as those showing the B[e] phenomenon and luminous blue variables (LBVs), undergo strong, often irregular mass ejection events. The prediction of these phases in stellar evolution models is therefore extremely difficult if not impossible. As a result, their effective temperatures, their luminosities and even their true nature are not fully known.Aims. A suitable procedure to derive the stellar parameters of these types of objects is to use the BCD spectrophotometric classification system, based on the analysis of the Balmer discontinuity. The BCD parameters (lambda_1 , D) have the advantage that they are independent of interstellar extinction and circumstellar contributions.Methods. We obtained low-resolution spectra for a sample of 14 stars with the B[e] phenomenon and LBVs. Using the BCD classification system, we derived the stellar and physical parameters. The study was complemented with information provided by the JHK colour-colour diagram.Results. For each star under investigation, the BCD system gives a complete set of fundamental parameters and related quantitiessuch as luminosity and distance. Among the 14 studied stars, we confirmed the classification of HK Ori, HD 323771 and HD 52721as pre-main sequence Herbig Ae/B[e] stars, AS 202 and HD 85567 as FS CMa-type stars, and HD 62623 as sgB[e]. We classified Hen 3-847, CD-24 5721, and HD 53367 as young B[e] stars or FS CMa-type candidates, and HD 58647 as a slightly evolved B[e] star.In addition, Hen 3-1398 is an sgB[e] and MWC 877, CPD-59 2854 and LHA 120-S 65 are LBV candidates. The stellar parameters of the latter two LBVs are determined for the first time. We also used the size-luminosity relation to estimate the inner radius of the dust disk around the pre-main and main sequence B[e] stars.Conclusions. Our results emphasise that the BCD system is an important and highly valuable tool to derive stellar parameters and physical properties of B-type stars in transition phases. This method can be combined with near-IR colour-colour diagrams to determine or confirm the evolutionary stage of emission-line stars with dust disks.